Child dental neglect and legal protections: a compendium of briefs from policy reviews in 26 countries and a special administrative region of China - Foláyan, Moréniké Oluwátóyìn; Ramos-Gomez, Francisco; Fatusi, Olawunmi Adedoyin; Nabil, Nouran; Lyimo, Germana V.; Minja, Irene Kida; Masumo, Ray M.; Mohamed, Nadia; Potgieter, Nicoline; Matanhire, Cleopatra; Maposa, Pamela; Akino, Chiedza Runyararo; et al. (Frontiers in Oral Health, 2023)
Background: Child neglect is a public health, human rights, and social problem, with potentially devastating and costly consequences. The aim of this study was to: 1) summarize the oral health profile of children across the globe; 2) provide a brief overview of legal instruments that can offer children protection from dental neglect; and 3) discuss the effectiveness of these legal instruments. Methods: We summarized and highlighted the caries profile and status of implementation of legislation on child dental neglect for 26 countries representing the World Health Organization regions: five countries in Africa (Nigeria, South Africa, Sudan, Tanzania, Zimbabwe), eight in the Americas(Argentina, Brazil, Canada, Chile, Mexico, Peru, Unites States of America, Uruguay), six in the Eastern Mediterranean(Egypt, Iran, Libya, Jordan, Qatar, Saudi Arabia), four in Europe(Italy, Latvia, Serbia, United Kingdom), two in South-East Asia (India and Indonesia) and one country (China) with its special administrative region (Hong Kong) in the Western Pacific. Results: Twenty-five of the 26 countries have legal instruments to address child neglect. Only two(8.0%) of these 25 countries had specific legal instruments on child dental neglect. Although child neglect laws can be interpreted to establish a case of child dental neglect, the latter may be difficult to establish in countries where governments have not addressed barriers that limit children’s access to oral healthcare. Where there are specific legal instruments to address child dental neglect, a supportive social ecosystem has also been built to facilitate children’s access to oral healthcare. A supportive legal environment, however, does not seem to confer extra protection against risks for untreated dental caries. Conclusions: The institution of specific country-level legislation on child dental neglect may not significantly reduce the national prevalence of untreated caries in children. It, however, increases the prospect for building a social ecosystem that may reduce the risk of untreated caries at the individual level. Social ecosystems to mitigate child dental neglect can be built when there is specific legislation against child dental neglect. It may be more effective to combine public health and human rights-based approaches, inclusive of an efficient criminal justice system to deal with child dental neglect.